Identidades de gênero e currículo: o discurso veiculado nos livros didáticos - Oliveira, Wilderlane Costa de (2014)
This research work aimed to verify which speeches about the constitutions of gender identities that pass over the textbooks for Portuguese language used in classes from 1st to 5th grade at municipal schools of the city of João Pessoa. The research was developed by observing the contexts and contributions of theories about identity, gender and discourse analysis. These theoretical knowledge provided conditions to identify and apprehend the gender relations that have been established in images and texts analyzed. The analysis consisted in checking and interpretation of representations about gender identities present in the texts and illustrations. Quantitatively were used five textbooks on which was initially performed a survey of representations and texts related to the topic under study, being cataloged 21 images and 19 texts that accounted for the relations of gender identities. The result of the analysis made the observation that there is a trend of assimilation of quantitative representations of male and female genders, however the context and the relations established between them still favors the process of male hegemony. This observation reinforces the need for a new look on the reading practices performed in various textual intakes, so that will make it possible to denaturalize the relations that are established between the genders in society.